A Comparative Analysis of Cloud-Based Information Systems Adoption in Small and Medium Enterprise - Soleman, Soleman (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The adoption of cloud-based information systems (CBIS) has significantly transformed operational efficiency and competitiveness among Small and Medium Enterprises (SMEs). However, adoption rates and implementation outcomes vary across different contexts, sectors, and regions. This study presents a comparative analysis of CBIS adoption among SMEs to identify key drivers, barriers, and performance impacts. Using a mixed-methods approach, data were collected through surveys and interviews from SMEs operating in manufacturing, services, and retail sectors across two distinct regions. The analysis was framed using the Technology-Organization-Environment (TOE) model and Diffusion of Innovation (DOI) theory. The findings reveal that technological readiness, perceived benefits, top management support, and regulatory environment significantly influence adoption decisions. Furthermore, SMEs that successfully adopted CBIS reported improved data accessibility, cost efficiency, and scalability, although challenges such as security concerns and lack of technical expertise persist. The study provides practical implications for SME decision-makers and policy recommendations for facilitating digital transformation in the SME sector.